Network and parallel computing : 10th IFIP International Conference, NPC 2013, Guiyang, China, September 19-21, 2013. Proceedings - Li, Xiaoming; Shi, Xuanhua; Zheng, Ran; Hsu, Ching-Hsien (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the 10th IFIP International Conference on Network and Parallel Computing, NPC 2013, held in Guiyang, China, in September 2013. The 34 papers presented in this volume were carefully reviewed and selected from 109 submissions. They are organized in topical sections named: parallel programming and algorithms; cloud resource management; parallel architectures; multi-core computing and GPU; and miscellaneous.